Comfort of formal and informal caregivers to palliative care patients in primary health care - Silmara Meneguin; Rafaela Ribeiro; Maria de Lourdes Silva Marques Ferreira (Rev Rene)
Objective: to analyze the comfort of formal and informal caregivers to palliative care patients, identifying the variables associated with the difficulties for home care. Methods: cross-sectional study involving 50 caregivers of palliative care patients attended in the Family Health Strategy, using the General Comfort Questionnaire. Results: most caregivers were women (86.0%), with a mean age of 52 years, with partners (68.0%) and practicing some religion (72.0%). The comfort scores ranged between 202 and 263, with a median of 235. An inverse relation was verified between the General Comfort Questionnaire score and caregiver reports of some difficulty in care delivery to palliative care patients (OR=0.90; 95.0% CI 0.81-1.01).Conclusion: the comfort level of the palliative care patients’ caregivers was relatively good and was associated with the difficulties in home care.